Similarities and Differences Between Vestibular and Cochlear Systems – A Review of Clinical and Physiological Evidence - Curthoys, Ian S.; Grant, John Wally; Pastras, Christopher J.; Fröhlich, Laura; Brown, Daniel J. (Frontiers in Neuroscience, 2021)
The evoked response to repeated brief stimuli, such as clicks or short tone bursts, is used for clinical evaluation of the function of both the auditory and vestibular systems. One auditory response is a neural potential — the Auditory Brainstem Response (ABR) — recorded by surface electrodes on the head. The clinical analogue for testing the otolithic response to abrupt sounds and vibration is the myogenic potential recorded from tensed muscles — the vestibular evoked myogenic potential (VEMP). VEMPs have provided clinicians with a long sought-after tool — a simple, clinically realistic indicator of the function of each of the 4 otolithic sensory regions. We review the basic neural evidence for VEMPs and discuss the similarities and differences between otolithic and cochlear receptors and afferents. VEMPs are probably initiated by sound or vibration selectively activating afferent neurons with irregular resting discharge originating from the unique type I receptors at a specialized region of the otolithic maculae (the striola). We review how changes in VEMP responses indicate the functional state of peripheral vestibular function and the likely transduction mechanisms allowing otolithic receptors and afferents to trigger such very short latency responses. In section “ELECTROPHYSIOLOGY” we show how cochlear and vestibular receptors and afferents have many similar electrophysiological characteristics [e.g., both generate microphonics, summating potentials, and compound action potentials (the vestibular evoked potential, VsEP)]. Recent electrophysiological evidence shows that the hydrodynamic changes in the labyrinth caused by increased fluid volume (endolymphatic hydrops), change the responses of utricular receptors and afferents in a way which mimics the changes in vestibular function attributed to endolymphatic hydrops in human patients. In section “MECHANICS OF OTOLITHS IN VEMPS TESTING” we show how the major VEMP results (latency and frequency response) follow from modeling the physical characteristics of the macula (dimensions, stiffness etc.). In particular, the structure and mechanical operation of the utricular macula explains the very fast response of the type I receptors and irregular afferents which is the very basis of VEMPs and these structural changes of the macula in Menière’s Disease (MD) predict the upward shift of VEMP tuning in these patients.